Papilledema and Echographically Detectable Retro-orbital Dilatation of the Sub-arachnoidal Space with open Fontanelle - Six Case Reports - Gusek-Schneider, G. C.; Mardin, Christian Y.; Trollmann, Regina; Eyüpoglu, Ilker Yasin; Ganslandt, Oliver Thomas (Klinische Monatsblätter für Augenheilkunde, 2011)
This paper analyses the case reports for three children in which a papilledema occurred before the age of one year. Furthermore, an analysis is also given of three further case reports for children aged less than one year in which, in spite of open fontanelle, no papilledema was found, however, a dilatation of the sub-arachnoidal space was demonstrated echographically. Even in children less than one year of age in which an open fontanelle still exists and in whom a neuro-paediatric clarification of internal hydrocepalus is made, in spite of opththalmoscopically inconspicuous findings for the papilla an echography is indispensable for the evaluation of the sub-arachnoidal space. Here, the early recognition of a dilatation of the retro-bulbar sub-arachnoidal space can possibly prevent the occurrence of a consecutive optic atrophy. At the present time, the data available do not allow the recommendation of an upper age limit for an echographic examination.
EVALuna2:21040